Meilensteine, Straßen und das Verkehrsnetz der Provinz Karia Milestones, Roads and the Transportation-System of the Province of Caria - Hild, Friedrich (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
Milestones are crucial for the scholarly research of roads and the transportation system of a province. Written and archaeological sources as well as the geographic conditions add to the overall picture.